Oligonucleotide Ligation Assay for Detecting Mutations in the Human Immunodeficiency Virus Type 1 pol Gene That Are Associated with Resistance to Zidovudine, Didanosine, and Lamivudine - Edelstein, Reva E. (American Society for Microbiology, 1998)
This report describes the detection of mutations in the pol gene of human immunodeficiency virus type 1 associated with resistance to zidovudine, didanosine, and lamivudine by genotyping by an oligonucleotide ligation assay specific codons in the pol gene amplified by PCR. Our studies demonstrate the sensitivity, simplicity, and specificity of this genotyping system.